The impacts of second-level land certification (SLLC) in Ethiopia: Empirical evidence using panel data - Ghebru, Hosaena; Girmachew, Fikirte (World Bank, 2019)
Ethiopia has implemented one of the largest, fastest and cheapest land registration and certification reforms in Africa. While there have been evidences of the positive impacts of this land reform in terms of increased investment, land productivity and land rental market activities, the government together with development partners is now piloting another round of land registration and certification that is financially and technically demanding - involving GPS measurement and computer registration. This ‘second stage land registration’ is expected to replace the registration from the first round that used general boundary (field markings) in combination with memory of the neighbors to identify plot borders.